(untitled) (American Journal of Islam and Society, 1992)
We are pleased to present the first summer issue of our new quarterly schedule. This will, in sha’ Allah, be followed by our fall issue in September 1992 and winter issue in December 1992. In this issue, Mahmoud Dhaouadi discusses the nature of human cultural symbols such as language, thought, religious beliefs, knowledge, cultural norms and values, and science. The essay develops a basic theoretical framework for studying the nature of what he describes as a cultural-symbolic soul. It then proceeds to apply this new concept to understandmg as well as devising a potential explanation of the dynamics of cultural-symbolic exchange and confrontation between human groups regardless of time and space constraints. Dhaouadi attempts to provide a balanced contribution to the ever-growing body of knowledge in the modem social and behavioral sciences by trying to work out a synthesis between theory and application, which, if executed successfully, would enhance the scientific credibility of the behavioral and social sciences. Dhaouadi pleads that by paying attention to other epistemologies, ideas, concepts, theories, and methodologies, an initial step could be taken towards resolving the crisis which the social sciences have been experiencing in the West since the 1970s. He believes that the continuing growth of the body of knowledge in the Islamic behavioral and social sciences will equip its practitioners with the knowledge to make constructive contributions to the reform of Western behavioral and social scientific thought. Muhammad Y. Faruqi traces the development of ijma’ from the practice of the Companions of the Prophet to the classical fuqaha’ . The jurists of the four established schools of fiqh consider ijma’, a concept which evolved as a legal doctrine during the second hijri century, as the third source after the Qur’an and the Sunnah. Farqui discusses the kinds of ijma’ and raises the issue of the infallibility of ijma’ . He argues that if the views of the classical jurists were adopted, in effect no one would be allowed to disagree or have a different opinion, as this would jeopardize the ummah’s infallibility. He supports Ibn Hazm’s view that consensus must be based on a nass from either the Qur’an, the hadith, or both. As these sources are infallible, any resulting consensus will also be infallible. He brings up the interpretation of al Juwayni, who states that there is no clear Qur’anic or hadith text referring to the principle of ijma’. Al Juwayni proves the authority of consensus by arguing that there are certain issues related to haram ...